Strategic Analysis of Development of Medical Tourism Macro-Destinations - BAIEV, Vadim Victorovych; BAKHOV, Ivan Stepanovych; FOKINA-MEZENTSEVA, Katerina; BORETSKA, Nataliya (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).10, 2019)
The article identifies the basic stages of the process of determining strategic objectives of a medical tourism destination. It suggests a range of tools for conducting a SWOT-analysis based on such analytical materials as Medical Tourism Index, World Economic Forum: Travel & Tourism Competitiveness Report, World Economic Forum: The Global Competitiveness Report. It also carries out a SWOT-analysis of macro-destinations of the leading countries in medical tourism.